2022
DOI: 10.3390/su14106167
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Strengths and Difficulties in Italian Adolescents: Analysis of Adaptation through the SDQ

Abstract: An adolescent’s knowledge of him/herself (positive aspects and weaknesses) is shaped by interactions with external and internal factors, including the family context and the educational environment. The assessment of this knowledge serves to construct the concept of self-esteem. The main objective of the present study was to examine the prevalence of self-reported emotional and behavioral symptoms in a representative sample of Italian adolescents and their relationship with gender and age, using Goodman’s Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…These findings suggest that adults fail to fully consider the extent of emotional distress experienced by the youth. In particular, students scored high for emotional symptoms, as indicated in other Italian studies that showed an increase in emotional difficulties during the acute phase of the pandemic (Corvasce et al, 2022;Pisano et al, 2021) with a deterioration of psychological well-being compared with the prepandemic period (Mastorci et al, 2021;Pedrini et al, 2022). Regarding students' behaviors, teachers perceived fewer issues on conduct problems than parents and this is probably because parents experienced greater proximity with their children during the pandemic due to the large amount of time spent indoors during the COVID-19 lockdown.…”
Section: Discussionsupporting
confidence: 62%
“…These findings suggest that adults fail to fully consider the extent of emotional distress experienced by the youth. In particular, students scored high for emotional symptoms, as indicated in other Italian studies that showed an increase in emotional difficulties during the acute phase of the pandemic (Corvasce et al, 2022;Pisano et al, 2021) with a deterioration of psychological well-being compared with the prepandemic period (Mastorci et al, 2021;Pedrini et al, 2022). Regarding students' behaviors, teachers perceived fewer issues on conduct problems than parents and this is probably because parents experienced greater proximity with their children during the pandemic due to the large amount of time spent indoors during the COVID-19 lockdown.…”
Section: Discussionsupporting
confidence: 62%
“…Comprising 25 items, the questionnaire employs a 3-point Likert scale (i.e., "Not true," "Partially true," and "Absolutely true") and is structured into five factors: emotional symptoms (ES; e.g., "Complaining of headache, stomach pain, or nausea"), conduct problems (CP; e.g., "Fights with other children or annoys them on purpose"), hyperactivity-inattention (HI; e.g., "Constantly moving or uncomfortable"), peer relationship problems (PRP; e.g., "Have at least one good friend"), and prosocial behaviours (PB; e.g., "Respectful of the feelings of others"). Studies support the original factor structure of the Goodman's questionnaire from early to late adolescence (10-19 years old, [48]), including Italian adolescents (until 18 years old, [49]). In the present study, acceptable reliability was demonstrated for each sub-scale (α ES = 0.76; α CP = 0.50; α HI = 0.64; α PRP = 0.55; and α PB = 0.59).…”
Section: Strengths and Difficulties Questionnaire (Sdq)mentioning
confidence: 67%
“…( 2010 ), and Corvasce et al . ( 2022 ) used the measure on an adolescent sample. The questionnaire showed good reliability, cross-informant correlation, and test-retest stability.…”
Section: Methodsmentioning
confidence: 99%